PENGARUH SETTING PERON TERHADAP ADAPTABILITAS PENGGUNA KRL STUDI KASUS: STASIUN KERETA API KEBAYORAN PADA JAM SIBUK - Khamdevi, Muhammar (Nalars, 2015)
ABSTRACT. The increasing population of Jakarta caused huge number of passengers of Commuter Line (KRL), especially during rush hour . For instance, Serpong Line (Serpong - Manggarai). The trip Frequency of Serpong Line has been no additions yet, though the number of passengers continues to increase. Kebayoran station has a very short platform, that made the passengers in difficult conditions (Dira, 2011) . The Limited wide of the platform and low platform type must bring difficulties. To go up and down the train, the passengers should use